Modeling Kebijakan Staffing, Cross-Training, Tour Scheduling, dan Assignment it Support Contact Center dengan Mempertimbangkan Skill Set - Hasna Nurhasanah; Dida Diah Damayanti; Mohammad Deni Akbar (Syntax Corporation, 2023)
Scheduling is an important activity to allocate existing resources so that a company can be more optimal. With good scheduling a company can do work effectively and can even make efficiency. Contact center is the central point or center of interaction between the company and customers managed by a company. The contact center plays a role in recognizing opportunities by collecting as much customer information as possible, making sales, and retaining customers. However, the contact center can only play an active role if it is complemented by the role of IT support which functions to choose the right technology, implement it correctly, and then maximize it from day to day. The success of the IT support division determines the success of the contact center as a whole. In this research, a procedure algorithm was developed to model staffing policies, cross-training, tour scheduling, and assignment of IT support contact centers by considering skill sets. This procedure algorithm starts by identifying demand needs for each skill, existing personnel capabilities, and preparing work schedules according to the efficiency of each personnel. The planning horizon used in this research is 1 week. Based on the PT XYZ case study, this algorithm provides benefits in terms of cost and fairness of schedule distribution for employees.